2005
DOI: 10.1681/asn.2005060664
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipid Modification on Progression of Coronary Calcification

Abstract: Coronary artery calcification (CAC) reflects the anatomic presence of coronary atherosclerosis and the relative burden of coronary artery disease (CAD). Higher levels of CAC are seen in the presence of CAD risk factors, older age, and chronic kidney disease. The lipid profile (primarily low HDL cholesterol, elevated triglycerides, elevated LDL cholesterol, and elevated total cholesterol) are important factors in the calcification process. The annual progression of CAC can be reduced from 25 to 30% to 0 to 6% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
1
17
1
1
Order By: Relevance
“…We speculated that greater use of sevelamer might have contributed to a potential benefit on the CAC process in these patients. A few studies have demonstrated that progressive CAC can be largely abolished by the use of sevelamer in place of CBPBs [11,12,25,39,40]. Also, the CACS increased in our three patients on dialysis (patients 1, 2 and 3).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…We speculated that greater use of sevelamer might have contributed to a potential benefit on the CAC process in these patients. A few studies have demonstrated that progressive CAC can be largely abolished by the use of sevelamer in place of CBPBs [11,12,25,39,40]. Also, the CACS increased in our three patients on dialysis (patients 1, 2 and 3).…”
Section: Discussionsupporting
confidence: 50%
“…In our study progression of CAC was associated with baseline levels of total cholesterol, baseline and final levels of LDL-cholesterol, and final serum albumin levels in univariate analysis. In several studies of adults with CKD, dyslipidemia, such as increased triglyceride level, total cholesterol and LDL-cholesterol levels or decreased highdensity lipoprotein (HDL)-cholesterol level, has been implicated in the progression of CAC [25,39,46,47]. The results of the Treat to Goal Study [11] suggest that the lowering of LDL-cholesterol level in adults with ESRD may also result in amelioration of the progression of CAC.…”
Section: Discussionmentioning
confidence: 99%
“…Age, sex, smoking, hypertension, dyslipidemia, chronic kidney disease, diabetes and hyperglycemia are all known risk factors for developing CAC [6,7,8]. However, it is still unclear whether dietary factors are significant independent risk factors for developing CAC.…”
Section: Introductionmentioning
confidence: 99%
“…Zu den Risikofaktoren einer Atherosklerose werden hohe Gesamtcholesterin-, hohe LDL-Cholesterin-, niedrige HDLCholesterin-sowie hohe Triglyceridspiegel im Blut gerechnet [13]. Laut einem Bericht der Centers for Disease Control and Prevention (CDC) sollen im Jahr 2009 in den USA 76% der Bevölkerung im Alter von 18 Jahren oder älter hinsichtlich hoher Cholesterinwerte gescreent worden sein.…”
Section: Ldl- Und Hdl-cholesterinunclassified